Platelet extracellular vesicles are superior to cardiac troponin to diagnose acute coronary syndrome with short symptom duration: LEMONADE trial. (3rd October 2022) - Gasecka, A; Budzianowski, J; Wawiorka, M; Palucha, K; Pieszko, K; Hiczkiewicz, J; Filipiak, K J; Grabowski, M; Falkema, K; Van Der Pol, E; Nieuwland, R
Abstract: Background: Acute coronary syndrome (ACS), which comprises acute myocardial infarction (AMI) and unstable angina pectoris (UAP), is one of the main causes of mortality worldwide. Cardiac troponin is the gold standard to diagnose AMI. Troponin has two main disadvantages: it is negative in patients with UAP but positive in other diseases. During ACS, activated platelets release extracellular vesicles (EVs), which promote coagulation and associate with fibrin, and contribute to thrombus formation. We hypothesized that the concentration and composition of circulating platelet EVs (1) change in blood of patients with ACS compared to patients with other causes of chest pain, and (2) thereby allow earlier diagnosis of ACS than cardiac troponin. Purpose: We aimed to determine the diagnostic value of circulating platelet EVs as novel early biomarkers of developing ACS. Methods: We conducted a prospective, multicentre trial enrolling 105 patients who presented to the emergency department with suspected ACS. Blood was collected at admission to measure the concentration of EVs and cardiac troponin. Flow cytometry (Apogee A60-Micro) was used to determine plasma concentrations of platelet EVs exposing P-selectin (CD61+/CD62p+) and fibrin (CD61+/fibrin+). Results: Plasma concentrations of platelet EVs exposing fibrin was lower in patients with ACS, compared to patients with other causes of chest pain (p=0.023) and lower in patients with an occlusive thrombus compared to non-occlusive plaque (p=0.015). Fibrin exposing-EVs were independent predictors of ACS (OR 8.2, CI 1.3–16.4) in multivariate analysis, allowing to diagnose ACS with 75% sensitivity and 72% specificity. Among patients with pain onset less than 2 hours before presentation, fibrin-exposing EVs had substantially better diagnostic performance than troponin (area under the ROC curve 0.90 vs. 0.74, respectively). Regarding other causes of chest pain, fibrin-exposing EVs were the lowest in patients with ACS, higher in patients with other cardiological causes of chest pain, and the highest in patients with non-cardiological causes of chest pain (p=0.036). Conclusions: Circulating fibrin-exposing EVs are early biomarkers of developing ACS, superior to cardiac troponin in patients with pain onset less than 2 hours before presentation. Incorporation of EV measurements into the ACS diagnostic algorithm might revolutionise thrombotic risk stratification in the emergency setting. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Specialised Research Fellowship, "Club 30" of the Polish Society of Cardiology